2019
DOI: 10.5194/acp-19-8721-2019
|View full text |Cite
|
Sign up to set email alerts
|

Is water vapor a key player of the wintertime haze in North China Plain?

Abstract: Abstract. Water vapor has been proposed to amplify the severe haze pollution in China by enhancing the aerosol–radiation feedback (ARF). Observations have revealed that the near-surface PM2.5 concentrations ([PM2.5]) generally exhibit an increasing trend with relative humidity (RH) in the North China Plain (NCP) during 2015 wintertime, indicating that the aerosol liquid water (ALW) caused by hygroscopic growth could play an important role in the PM2.5 formation and accumulation. Simulations during a persistent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…The anomalous southerly flows give rise to the accumulation of pollutants and moisture over Beijing, with reduced surface wind speeds, which is conducive to the accumulation of air pollutants (Wu et al 2017). Abundant moisture over the Beijing region enhances aerosol scattering and secondary aerosol formation, resulting in the accumulation of pollutants (Wu et al 2019. Figure S2 depicts correlation coefficients between anomalous variables of atmospheric circulation from the near-surface to the upper troposphere and the intensity of haze days in Beijing in winter from 1980 to 2017.…”
Section: Both Anthropogenic Emissions and Climatic Conditions Determimentioning
confidence: 99%
“…The anomalous southerly flows give rise to the accumulation of pollutants and moisture over Beijing, with reduced surface wind speeds, which is conducive to the accumulation of air pollutants (Wu et al 2017). Abundant moisture over the Beijing region enhances aerosol scattering and secondary aerosol formation, resulting in the accumulation of pollutants (Wu et al 2019. Figure S2 depicts correlation coefficients between anomalous variables of atmospheric circulation from the near-surface to the upper troposphere and the intensity of haze days in Beijing in winter from 1980 to 2017.…”
Section: Both Anthropogenic Emissions and Climatic Conditions Determimentioning
confidence: 99%
“…Huang et al (2019) further found that concurrent changes in the location of the subtropical and polar front jet in East Asia in winter has an important impact on the climate of East Asia. In addition, previous studies showed that the North Atlantic was a source of teleconnection waves, where anomalies in atmospheric circulation related to sea surface temperatures (SSTs) can significantly influence winter weather in the Northern Hemisphere (Wallace and Gutzler, 1981;Peng et al, 1995;Czaja and Frankignoul, 2002;Li and Bates, 2007) and can influence haze in China (Xiao et al, 2014;Gao and Chen, 2017). Chen et al (2013) noted that cold air outbreaks were possibly associated with the development of the Siberian high pressure and a wave train from the North Atlantic.…”
mentioning
confidence: 99%
“…On the other hand, the average RH reached as high as 91.7%, which was approximately 1.3 times higher than the first period. Increasing RH facilitates the aerosol hygroscopic growth and further enhances the aerosol liquid water, facilitating the secondary aerosols formation by serving as an important medium for liquid-phase and heterogeneous reactions [26]. Therefore, high RH will increase PM 2.5 concentrations and worsen pollution.…”
Section: Summary Of a Haze Episodementioning
confidence: 99%
“…High RH played an important role in the formation of PM 2.5 . However, when RH > 80%, PM 2.5 concentrations began to decrease due to the high frequency of precipitation [25,26].…”
Section: Introductionmentioning
confidence: 99%